2017
DOI: 10.1007/s11307-017-1116-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Caffeine Consumption on the Adenosine A1 Receptor in the Rat Brain: an In Vivo PET Study with [18F]CPFPX

Abstract: The present study provides evidence that chronic caffeine consumption does not lead to persistent changes in functional availability of cerebral AARs which have previously been associated with neuroprotective effects of caffeine. The acute and region-specific decrease in cerebral AAR availability directly after caffeine withdrawal is most likely caused by residual amounts of caffeine metabolites disguising an unchanged AAR expression at this early time-point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
11
0
3
Order By: Relevance
“…It has also been utilized to visualize and quantify the in vivo occupancy of the human cerebral adenosine A 1 receptor by caffeine [34], and demonstrated that its chronic use did not lead to persistent changes in functional availability of A 1 ARs [35].…”
Section: Radioligands and Radiotracersmentioning
confidence: 99%
“…It has also been utilized to visualize and quantify the in vivo occupancy of the human cerebral adenosine A 1 receptor by caffeine [34], and demonstrated that its chronic use did not lead to persistent changes in functional availability of A 1 ARs [35].…”
Section: Radioligands and Radiotracersmentioning
confidence: 99%
“…It is also impossible to ignore the different part of the investigated structures in the hypothalamic-pituitary-adrenocortical axis. Since caf-feine is a nonselective adenosine antagonist, it can modulate the metabolic pathways in this axis (Nabbi-Schroeter et al, 2018;Karaismailoglu et al, 2017;Xu et al, 2012), which will somehow affect the adaptive responses. First of all, it concerns adrenal glands that react sensitively to the formation and implementation of adaptive-compensatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Pagnussat et al believe that A2ARs are necessary and sufficient for triggering memory impairment, and A1R may selectively participate in controlling memory impairment driven by cholinergic processes. Nabbi‐Schroeter et al suggested that caffeine, a nonselective antagonist of adenosine receptors, may protect against neuronal degeneration and death caused by β‐amyloid by blocking A2AR and observed that the A2BR antagonist has a certain protective effect against AD. In addition, there is an association between isoflurane exposure and spatial memory impairment, and declines in NR2B levels and increases in Aβ and P‐tau levels may be achieved by activating A1AR .…”
Section: The Role Of Adenosine and Its Receptors In Central Nervous Smentioning
confidence: 99%